Pemberdayaan Bumdes Bojonegoro Melalui Kemandirian Pengelolaan Website - Putra, S.E., MSA, Rediyanto; Kusumaningtias, Rohmawati; Pujiono, Pujiono; Siregar, Cantika Sari; Hidayat, Rendra Arief; Prasetyo, Eko (Abimanyu : Jornal of Community Engagement, 2023)
This service activity will be carried out at BUMDES located in Kapas Village, Kapas District, Bojonegoro Regency, East Java. This group experienced several problems, namely the lack of knowledge about the use of Information and Communication Technology for BUMDES businesses and the unavailability of BUMDES website media that can be used to manage and disseminate information to the public. Therefore, this activity provides solutions as follows: training on the use of Information and Communication Technology to BUMDES managers and the creation of websites and YouTube accounts as BUMDES media for digitally managing and disseminating information. The methods used in this community service activity are field surveys, lectures, demonstrations, practices, discussions, and distributing questionnaires. This PkM activity has been going well as shown from the results of the PkM activity survey that has been given to participants. This PkM activity succeeded in providing a number of outcomes that were given to partners in the form of website products, youtube accounts, and simple excel-based financial applications. In addition, this PkM also provides knowledge partners that can be used to manage the BUMDES business that has been run so that it becomes even better.